De la modernisation écologique à la résilience : un réformisme de plus? - Florence Rudolf (VertigO, 2013)
The ecological modernization, invented in the 80’s as a response to the ecological crisis, can it be considered as a prefiguration of a resiliency’s program? This proposition is grounded on the argument that the ecological modernization follows an adaptation’s strategy of our lifestyles to ecological constraints. Following this proposition we study the ecological modernization as it has be conceived in the 80’s and as it is observed nowadays on the base of the feed back from countries and regions that have tried this program. The ecological modernization is built on a new alliance between economy and ecology and on a new conception of public policy. This alliance is grounded on the challenge that technological and scientific innovations will help to face the ecological crisis. This program that has been experimented in the northern European countries since ten to twenty years shows some limits as for example maintaining the illusion of a consensus on the ecological crisis. This illusion did not actively help in a change of paradigm. Does the success of resilience open a new wave of illusion concerning our capacity to reform our social and economic system? The reflections engaged by our German colleagues in the history and sociology of environment sounds like a warning? Does resilience really announce a substitution program or does it make illusion in her turn? It is what we shall once discuss in this paper.